Frequency, characterization and genotypic analysis of Shiga toxin-producing Escherichia coli in beef slaughterhouses of Argentina = Frecuencia, caracterización y análisis genotípico de Escherichia coli productor de toxina Shiga en frigoríficos de carne bovina de Argentina - Cap, Mariana; Carbonari, Claudia Carolina; D’Astek, Beatriz A.; Zolezzi, Gisela; Deza, Natalia; Palladino, Pablo Martin; Masana, Marcelo Oscar; Chinen, Isabel; Rivas, Marta (2019)
The objectives of this study were: (1) to estimate STEC frequency in hide and carcass samples taken from beef slaughterhouses supplying the domestic market in Argentina, (2) to establish the pheno-genotypic characteristics of STEC and non-toxigenic Escherichia coli of serogroups O26, O45, O103, O121, O111, O145 or O157 isolated from the analyzed samples and, (3) to study their clonal relatedness. Sixty hides and 60 carcasses were analyzed. At the screening step, 48% of hide and 80% of carcass samples tested positive for the stx gene by endpoint PCR. The STEC isolation rate was 5% for hides and 8% for carcasses. The isolation rate of STEC-positive for O26, O45, O103, O111, O145 or O157 serogroups was 0% for hides and 2% for carcasses. With the purpose of studying the clonal relatedness of isolates, macrorestriction fragment analysis by pulsed-field gel electrophoresis was performed. The results indicated cross-contamination between hides and between carcasses of animals in the same lot and, that the origin of carcass contamination was their own hide, or the hides of other animals in the same lot. The high detection rate at the screening step, especially in carcasses, and the evidence of cross-contamination show the need to apply additional in-plant intervention strategies aimed at preventing carcass contamination.